The Multifaceted Biological Activities of Hydantoin Derivatives: From Antimicrobial to Anticancer Agents - Bhadreshkumar. R. Sudani, (The Bioscan, 2024)
Hydantoin derivatives, a versatile class of heterocyclic compounds, have garnered significant attention in recent years due to their diverse biological activities. These derivatives exhibit a wide range of pharmacological properties, making them valuable candidates in the development of therapeutic agents. This review highlights the multifaceted biological activities of Hydantoin derivatives, with a focus on their antimicrobial and anticancer properties. The antimicrobial efficacy of these compounds encompasses activity against various bacterial, fungal, and viral pathogens, presenting them as potential alternatives to conventional antibiotics. Additionally, Hydantoin derivatives have shown promising anticancer activities by inducing apoptosis, inhibiting cell proliferation, and interfering with various cellular signaling pathways. The structural modifications of these derivatives play a crucial role in enhancing their biological activities, providing insights into structure-activity relationships. Moreover, their potential to overcome drug resistance and reduce side effects associated with traditional therapies underscores their therapeutic significance. This review aims to provide a comprehensive overview of the recent advancements in the biological applications of Hydantoin derivatives, emphasizing their role as promising candidates for future drug development in antimicrobial and anticancer therapy. Further research and clinical studies are warranted to fully explore their therapeutic potential and translate these findings into clinical practice.